Catalogue-on-Tape (Non-conventional Methods in Document Retrieva1. 5) - Venkata Raman, S.; Neelameghan, A. (Journal of Information and Knowledge, 1968)
Describes the steps in the preparation of the Cataiogue-on-Tape forming the input to the computer-based document finding system. The format of the entry for a document, preparation of the punched card, sorting, and transfer of the entries on to magnetic tape to form the store, are explained. The step-by-step procedure and flow-chart in the transfer of the entries on to magnetic tape, and amending this list of documents, are given.